Effects of paternal age and interaction with smoking, alcohol consumption and maternal age on implantation failure in women undergoing ART - Jiaqian Yin; Ruoling Chen; David Churchill; Huijuan Zou; Peipei Guo; Chunmei Liang; Xiaoqing Peng; Jieyu Wang; Zhikang Zhang; Weiju Zhou; Yunxia Cao (Scientific Reports)
Abstract It remains unclear whether there is an independent association of paternal age with implantation failure (IF) in couples undergoing Assisted Reproductive Technology (ART) treatment. Little is known about the interactive effects of paternal age with maternal age, paternal smoking and alcohol consumption on IF. The Anhui Maternal-Child Health Cohort Study (AMCHS) interviewed 1910 infertile couples (paternal age ranged 22–57 years) to look for risk factors associated with IF. Implantation outcome was assessed using serum β-HCG between 0 and 25 IU/L 14 days post-embryo transfer. Odds ratios (ORs) for IF in relation to paternal age, and its interactions with maternal age, paternal smoking and alcohol consumption were evaluated using logistic regression models. The risk of IF (n = 735) increased with paternal age ≥ 35, while it remained similarly lower among males aged 22–34. After adjusting for socioeconomic status,  paternal lifestyles and semen factors, the OR for IF was 1.50 (95%CI 1.16–1.93) at paternal age of 35-<40 years, 2.06 (1.34–3.16) at 40-<45 years and 3.80 (2.50–7.07) at ≥ 45 years in comparison to those aged < 35. With additional adjustments for maternal age and maternal factors including anovulation and antral follicle counting, the corresponding ORs were 1.19 (0.89–1.60), 1.31 (0.79–2.16) and 2.13 (1.06–4.29). The association remained significant in those with maternal age > 30, paternal smoking or alcohol consumption, but not in their counterparts, respectively. Among those with a paternal age ≥ 35, each additional year of smoking was associated with a 7.0% increased risk of IF (OR = 1.07, 95% CI: 1.01–1.14); however, no such association was observed in younger paternal age groups. Significant interaction effects were observed between advanced paternal age and maternal age, as well as paternal alcohol consumption. The AMCHS had demonstrated that paternal age ≥ 35 years elevates the risk of IF, with additional impacts from advanced maternal age and paternal alcohol consumption. The findings of the AMCHS highlight the need to consider paternal and maternal ages in fertility planning and suggest that IF can be reduced by stopping paternal smoking and alcohol consumption.